Elucidating the Biomechanics of Leukocyte Transendothelial Migration by Quantitative Imaging - Schwartz, Amy B.; Campos, Obed A.; Criado-Hidalgo, Ernesto; Chien, Shu; del Álamo, Juan C.; Lasheras, Juan C.; Yeh, Yi-Ting (Frontiers in Cell and Developmental Biology, 2021)
Leukocyte transendothelial migration is crucial for innate immunity and inflammation. Upon tissue damage or infection, leukocytes exit blood vessels by adhering to and probing vascular endothelial cells (VECs), breaching endothelial cell-cell junctions, and transmigrating across the endothelium. Transendothelial migration is a critical rate-limiting step in this process. Thus, leukocytes must quickly identify the most efficient route to make their way through VEC monolayers to facilitate a prompt innate immune response. Biomechanics plays a decisive role in transendothelial migration, which involves intimate physical contact and force transmission between the leukocytes and the VECs. While quantifying these forces is still challenging, recent advances in imaging, microfabrication, and computation now make it possible to study how cellular forces regulate VEC monolayer integrity, enable efficient pathfinding, and drive leukocyte transmigration. Here we review these recent advances, paying particular attention to leukocyte adhesion to the VEC monolayer, leukocyte probing of endothelial barrier gaps, and transmigration itself. To offer a practical perspective, we will discuss the current views on how biomechanics govern these processes and the force microscopy technologies that have enabled their quantitative analysis, thus contributing an improved understanding of leukocyte migration in inflammatory diseases.